The challenges of using biodata in promotional filmmaking - Reeves, Stuart; Martindale, Sarah; Tennent, Paul; Benford, Steve; Marshall, Joe; Walker, Brendan (Association for Computing Machinery, 2015)
We present a study of how filmmakers collected and visualised physiological data---'biodata'---to construct a series of short promotional films depicting people undergoing 'thrilling' experiences. Drawing on ethnographic studies of two major advertising campaigns, we highlight key concerns for integrating sensors and sensor data into film production. Our findings address the perceived benefits of using biodata within narratives; the nature of different on-screen representations of biodata; and the challenges presented when integrating biodata into production processes. Drawing on this, we reconsider the nature of information visualisation in the filmmaking context. Further implications from our case studies provide recommendations for HCI collaborations with filmmaking and broadcast industries, focussing both on the practical matters of fitting sensor technologies into and handling data within production workflows, as well as discussing the broader implications for managing the veracity of that data within professional media production.